Evidence of a locus for orofacial clefting on human chromosome 6p24 and STS content map of the region. - Davies, A; Stephens, R; Olavesen, MG; Heather, L; Dixon, M; Magee, A; Flinter, F; Ragoussis, I (1995)
Orofacial clefting is genetically complex, no single gene being responsible for all forms. It can, however, result from a single gene defect either as part of a syndrome (e.g. van der Woude syndrome, Treacher-Collins syndrome, velo-cardio-facial syndrome) or as an isolated phenotypic effect (e.g. X-linked cleft palate; non-syndromic, autosomal dominant orofacial clefting). Several studies have suggested that chromosome 6p is a candidate region for a locus involved in orofacial clefting. We have used YAC clones from contigs in 6p25-p23 to investigate three unrelated cases of cleft lip and palate coincident with chromosome 6p abnormalities. Case 1 has bilateral cleft lip and palate and a balanced translocation reported as 46,XY,t(6,7)(p23;q36.1). Case 2 has multiple abnormalities including cleft lip and palate and was reported as 46,XX,del(6)(p23;pter). Case 3 has bilateral cleft lip and palate and carries a balanced translocation reported as 46,XX,t(6;9)(p23;q22.3). We have identified two YAC clones, both of which cross the breakpoint in cases 1 and 3 and are deleted in case 2. These clones map to 6p24.3 and therefore suggest the presence of a locus for orofacial clefting in this region. The HGP22 and AP2 genes, potentially involved in face formation, have been found to flank this region, while F13A maps further telomeric in 6p24.3/25.